THE CITY CHARTER AND THE REVISED ORDINANCES OF THE CITY OF PEORIA, ILLINOIS 254 (James M. Cunningham ed., 1869) § 1 - (:unkn) unknown (General Publisher, 1869)
Prohibited the discharge of any cannon, musket, rifle, fowling-piece, pistol, or other fire-arms or air-guns. Violators fined not less than one but no more than one hundred dollars. Violators also forfeit the weapon.
--
Keywords: DISCHARGE